Socio-Psychological Aspects of the “Accessibility” of Works of Art - Rapoportas, Sergejus (Problemos, 1973)
The author discusses the rather general attitude prevailing in the sphere of art consumption when the recipient’s incomprehension of a specific work of art is being evaluated by him and his surroundings not “purely aesthetically”, but as a certain social characteristic of the recipient or the author in question. The author proceeds from the point that relations between the recipient and art are regulated by a number of cultural standards of diverse historical origin. Thus the very privity to art is ascribed to a member of society as a kind of behaviour adding to his prestige. As a result, “accessibility” or “inaccessibility” of works of art is evaluated by recipients as a certain index of their proximity to the socially encouraging norm (i.e., either due to “cultural backwardness” of consumers or to “bad quality” of the work itself and the author being put of touch with demands of the public).